Distinct binding affinities of odorant-binding proteins from the natural predator Chrysoperla sinica suggest different strategies to hunt prey. (November 2018) - Li, Zhao-Qun; Zhang, Shuai; Cai, Xiao-Ming; Luo, Jun-Yu; Dong, Shuang-Lin; Cui, Jin-Jie; Chen, Zong-Mao
Graphical abstract: Highlights: 12 CsinOBPs showed distinct expression patterns and motif-pattern. Their odorant binding spectrums were characterized in vitro . CsinOBP1 binds plant volatiles and aphid alarm pheromone (E)-beta-farnesene. Abstract: Chrysoperla sinica is an important natural predator of many notorious agricultural pests. Understanding its olfactory mechanism can help enhance the effectiveness of C. sinica in biological control. In the present study, we investigated the tissue expression patterns of 12 odorant-binding protein (OBP) genes from C. sinica ( CsinOBP s). The results of quantitative real-time polymerase chain reaction (qPCR) showed that CsinOBP1, CsinOBP2, CsinOBP3, CsinOBP4, CsinOBP6, CsinOBP7, CsinOBP9, CsinOBP10, and CsinOBP12 were predominantly expressed in the antennae of both sexes, indicating their roles in olfaction. Additionally, the qPCR analysis revealed that the 12 CsinOBP genes had distinct expression patterns, while the motif-pattern investigation suggested that the OBPs had different ligands. The ligand-binding assay showed that CsinOBP1 and CsinOBP10 had broader binding spectra than did the other OBPs. Thus, CsinOBP1 was able to bind not only plant volatiles (such as farnesol, cis -3-hexenyl hexanoate, geranylacetone, β-ionone, 2-tridecanone, and trans -nerolidol) but also the aphid alarm pheromone ( E )-β-farnesene. On the other hand, CsinOBP2 and CsinOBP6 exhibited relatively narrow binding spectra, only binding ethyl benzoate. The study also identified several compounds that can potentially be used to develop slow-release agents attracting C. sinica and to improve search strategies for insect pest control.